Facilitating drug delivery in the central nervous system by opening the blood-cerebrospinal fluid barrier with a single low energy shockwave pulse - Kung, Yi; Chen, Kuan-Yu; Liao, Wei-Hao; Hsu, Yi-Hua; Wu, Chueh-Hung; Hsiao, Ming-Yen; Huang, Abel P.-H.; Chen, Wen-Shiang (Fluids and barriers of the CNS, 2022)
The blood-cerebrospinal fluid (CSF) barrier (BCSFB) is critically important to the pathophysiology of the central nervous system (CNS). However, this barrier prevents the safe transmission of beneficial drugs from the blood to the CSF and thus the spinal cord and brain, limiting their effectiveness in treating a variety of CNS diseases. This study demonstrates a method on SD rats for reversible and site-specific opening of the BCSFB via a noninvasive, low-energy focused shockwave (FSW) pulse (energy flux density 0.03 mJ/mm ) with SonoVue microbubbles (2 × 10 MBs/kg), posing a low risk of injury. By opening the BCSFB, the concentrations of certain CNS-impermeable indicators (70 kDa Evans blue and 500 kDa FITC-dextran) and drugs (penicillin G, doxorubicin, and bevacizumab) could be significantly elevated in the CSF around both the brain and the spinal cord. Moreover, glioblastoma model rats treated by doxorubicin with this FSW-induced BCSFB (FSW-BCSFB) opening technique also survived significantly longer than untreated controls. This is the first study to demonstrate and validate a method for noninvasively and selectively opening the BCSFB to enhance drug delivery into CSF circulation. Potential applications may include treatments for neurodegenerative diseases, CNS infections, brain tumors, and leptomeningeal carcinomatosis.